Cross-Cultural Engineering: The role of Dutch civil engineering in modern port planning in Japan (1870s-1890s) - Iwamoto, Kazumasa; Hein, Carola (International Planning History Society Proceedings, 2018)
This is particularly true for the Japanese case, where civil engineering has played a major role in the country’s modernization and westernization since the mid-19th century. The design and engineering of Japanese ports from the 1870s to 1890s is a case in point. This contribution explores the degree to which civil engineering engaged with port city design by studying investigative reports, design drawings and survey maps established by Dutch civil engineers in collaboration with Japanese practitioners. It identifies three types of cross-cultural engineering. 1. Building a new port: Some Dutch engineers proposed complex projects combining water management and port basins, jetties with urban form, but these were only partially implemented. 2. Improvement of Port Functions: The Japanese engineers were particularly receptive for the design of breakwaters, the practice of dredging and the construction of basins; notably the technique of breakwaters became a staple in textbook and spread through Japan. 3: Development of the Port. The engineers developed a complete vision for a new port, but diverse reasons hindered realization, including natural features that disturbed the construction of the port. These three types stand as examples of the intricacies of cross cultural engineering in engineering and planning.